An Agenda for Comparing Local Governance and Institutional Collective Action in Canada and the United States. Issue 3 (May 2019) - Zeemering, Eric S.
As neighboring federal systems, Canada and the United States provide an opportunity to compare institutional collective action (ICA) by proximate local governments. After explaining the importance of understanding local governance in Canada and the United States in comparative context, the ICA framework is used to highlight propositions along two paths of inquiry. First, the ICA framework can be used to compare responses to ICA dilemmas in two distinct systems of local governance, focusing on the comparative instance of use and performance of ICA mechanisms. Second, the ICA framework can be used to analyze collaboration and paradiplomacy across the international border. Deploying the ICA framework for comparative research can improve our understanding of local governance and local government reform in both countries.